Atlas of Immunology - Cruse, Julius M Lewis, Robert E (CRC PRESS, 2010)
""This heavyweight offering could be a vade mecum for the infectious disease researcher. It covers the whole of immunology from A blood group to zymosan in easy-to-read bites."--Brian Henderson, University College London, in Microbiology Today" ""A beautifully illustrated and appealing discussion of the history of immunology ... clinical and research immunologists will delight in the book as the showpiece of a personal library."--Leaf L. Wallman, Department of Clinical Immunology and Allergy, Westmead Hospital, Australia, for the World Allergy Association" ""A well-illustrated encyclopedic dictionary ... this handy work contributes significantly to this rapidly advancing discipline ... Summing up: Highly recommended."---Choice" "Written in a highly readable, two-column format, this complete reference covers a wide array of subjects, with content ranging from photographs of field pioneers to illustrations of molecular structures of recently characterized cell receptors, chemokines, and cytokines. The atlas also addresses the major histocompatability complex molecules, immunoglobulins, hematopoietic cells in leukemia, and molecules of related interest to immunologists. You won't find another publication anywhere that matches the breadth or detail of illustrated immunological concepts."--Jacket.